Contribution to the development of new organic materials for optoelectronics: characterization, structure and related properties - BOUDJENANE, Fatima Zohra (l’Université de Mostaganem, 2024)
This study focuses on synthesizing and thoroughly analyzing two different compounds. The first compound (Z)-3-N-(ethyl)-2-N’-((3-methoxyphenyl)imino)thiazolidine-4-one (EMTh) was characterized using FT-IR, 1H and 13C NMR spectroscopy, and single-crystal X-ray diffraction. The crystal structure analysis revealed a non-planar molecular configuration with a notable 86.0° dihedral angle between the benzene and thiazolidinone rings. The crystal's molecular arrangement was controlled by C-H•••O and C-H•••N hydrogen bonds, leading to a unique three-dimensional packing pattern. Quantum chemical simulations employing the B3LYP/6-311G(d,p) theory level revealed information about the molecule's electrostatic potential, HOMO-LUMO energy levels, and dipole moment orientations, validating the compound's stability and charge transfer capabilities. Subsequent analyses, such as reduced density gradient, natural bond orbital, and Hirshfeld surface analysis, identified intrinsic non-bonded interactions and interatomic linkages that impact the crystal structure. The ligand showed strong biological activity by establishing significant interactions with amino acids in the protein (PDB ID: 2AZ5), leading to a binding energy of -6.3 kcal/mol and effectively inhibiting necrosis tumour factor. The second compound (Z)-2N- (tert-butylimino)-3N’-(4-methoxyphenyl) thiazolidin-4-one (TMTh) was synthesized and examined by1H and 13C NMR, and FT-IR spectroscopy techniques. The monoclinic crystal structure containing eight molecules in the unit cell was determined using the single-crystal X-ray diffraction method. Density functional theory (DFT) calculations gave optimized molecular geometry in good agreement with experimental results. Weak interactions such as C-H⋅⋅⋅O and C-H⋅⋅⋅S hydrogen bonds and van der Waals interactions important for crystal packing were identified using Hirshfeld surface (HS) and RDG methods. PED analysis helped determine vibration frequencies, supported by experimental FT-IR data. Time-dependent density functional theory (TD-DFT) was used to study electronic transitions, charge transfer, and UV-vis spectra. Frontier molecular orbitals (FMOs), and Molecular Electrostatic Potential (MEP) distribution maps offered insights into charge transfer and reactivity. Significant nonlinear optical (NLO) activity was also predicted by computational simulations. Computational ADMET analysis, such as molecular docking, assessed physicochemical properties, pharmacokinetics, and biological impacts on certain receptors. This study provides a thorough examination of the structural, electronic, and biological properties of the synthesized molecule. Finally, by conducting extensive molecular dynamics (MD) simulations, we have uncovered the compound's ability to inhibit selected enzymes and its corresponding binding properties, providing crucial insights for its potential therapeutic use. The binding energies were calculated using MM-PBSA.
Keywords: EMTh, TMTh, FT-IR, NMR, NLO, ADMET analysis, MD simulations, and MM-PBSA